Emerging therapies for mitochondrial disorders. (3rd May 2016) - Nightingale, Helen; Pfeffer, Gerald; Bargiela, David; Horvath, Rita; Chinnery, Patrick F.
Abstract : Traditionally, mitochondrial disorders have been treated with vitamins, co-factors and nutritional supplements with no proven benefit. While effective treatments are still lacking, several new molecular and cellular strategies have recently been proposed. Nightingale et al. critically appraise the most promising preclinical developments. Abstract : Abstract : Mitochondrial disorders are a diverse group of debilitating conditions resulting from nuclear and mitochondrial DNA mutations that affect multiple organs, often including the central and peripheral nervous system. Despite major advances in our understanding of the molecular mechanisms, effective treatments have not been forthcoming. For over five decades patients have been treated with different vitamins, co-factors and nutritional supplements, but with no proven benefit. There is therefore a clear need for a new approach. Several new strategies have been proposed acting at the molecular or cellular level. Whilst many show promise in vitro, the clinical potential of some is questionable. Here we critically appraise the most promising preclinical developments, placing the greatest emphasis on diseases caused by mitochondrial DNA mutations. With new animal and cellular models, longitudinal deep phenotyping in large patient cohorts, and growing interest from the pharmaceutical industry, the field is poised to make a breakthrough.